A mobility‐aware cluster‐based MAC protocol for radio‐ frequency energy harvesting cognitive wireless sensor networks. (10th June 2021) - Obaid, Arif; Fernando, Xavier; Jaseemuddin, Muhammad
Abstract: Cognitive wireless sensor networks (CWSN) are severely energy constrained and radio frequency (RF) wireless energy harvesting (RFWEH) has been shown to improve the network lifetime. In many CWSN applications, node mobility imposes challenges owing to changing network topology. Therefore, the design of a new medium access control (MAC) protocol that can handle node mobility as well as energy harvesting is required. A cluster‐based multihop MAC protocol (RMAC‐M) is proposed that incorporates RF energy harvesting in a mobility‐aware CWSN. Our protocol selects cluster heads using an algorithm based on an R‐factor parameter consisting of residual node energy, residual node data and node speed, with appropriate weights. It then transmits data packages using a multitier super cluster head routing mechanism without the need for neighbour discovery. The multitier clustering and RFWEH mechanisms boost the energy performance of the network, increasing its lifetime. On the other hand, time slots allocated for RFWEH increase delay, thereby affecting system latency. Owing to its unique nature, the proposed algorithm has no comparable protocols in the literature. For the sake of completeness, RMAC‐M is compared with well‐known MAC protocols such as LEACH‐M and KoNMAC that do not have energy harvesting or mobility features. Simulation results show that the proposed protocol increases the lifetime of the CWSN nodes substantially, promising a self‐sustainable network in terms of energy. Furthermore, despite the allocation of time slots for energy harvesting, critical network parameters such as throughput, packet loss and average delay remain within target levels.